Applications of coherent Raman scattering microscopies to clinical and biological studies. Issue 12 (21st June 2015) - Schie, Iwan W.; Krafft, Christoph; Popp, Jürgen
<x xml:space="preserve">Abstract</x> This review provides an update on coherent Raman scattering microscopy of cells and tissues since 2008 including CARS and SRS.